Analisis Kritis Filosofis Epistemologi Irfani dalam Tradisi Spritualisme Islam - Muhammad Adres Prawira Negara (Gunung Djati Conference Series, 2022)
Science is currently one of the factors that lead to the progress of mankind. However, this does not suddenly come without the dynamics in obtaining it. Basically, humans have various tools to be used as sources of knowledge, including the five senses used to analyze external objects, the mind used to process the objects obtained, and the heart is a source of knowledge that obtains internal objects that are present in the human soul. The purpose of this study is to examine the epistemology of Irfani in the Islamic tradition. In preparing this research, the researcher used a qualitative method with a literature study approach. The results of this study explain the source of knowledge in Islam, namely irfani in depth. When humans have reached the peak of the stages to gain irfani knowledge, then it can be ascertained that one's heart is pure.